KAJIAN KONSEP RASIONAL DAN MASLAHAH DALAM PENGEMBANGAN PERBANKAN SYARIAH: STUDI PERBANDINGAN ANTARA INDONESIA DAN MALAYSIA - Wiranatakusuma, Dimas Bagus; Muqorobin, Masyhudi; Yuliadi, Imamudin (Jurnal Ekonomi & Studi Pembangunan, 2016)
The main idea about preference and utility in Islamic perspective is to describe consumer behavior in accordance with the concept of maslahah. This essay tries to replicate the concept of maslahah by dividing into good deeds (G) and bad deeds (B) with certain limits of ability (A). The Hicksian and Marshallian demand function is used to recover the problem by taking the comparison of Islamic banking objects between Indonesia and Malaysia. This paper uses several selected variables to measure the function of Masahah (M) as well as the ability (A). Empirically, the variables used to measure the function of Masahah are savings, financing, and yield rate. In addition, the Cobb-Douglas (CD) utility function is used to describe the maslahah model. The study results show that Indonesia has a bigger problem compared to Malaysia based on its Shariah banking practices. However, more business has to be done by the Sharia Bank in Indonesia to maintain the maslahah level than in Malaysia because maslahah is seen as a manifestation of good effort (Eg).